Eveningness associates with smoking and sleep problems among pregnant women. (28th May 2017) - Merikanto, Ilona; Paavonen, E. Juulia; Saarenpää-Heikkilä, Outi; Paunio, Tiina; Partonen, Timo
ABSTRACT: Sleep problems during pregnancy impair maternal health and increase the risk for adverse pregnancy outcome. The circadian preference toward eveningness has been associated with sleep problems in previous studies. Here, we studied whether evening-type women had more sleep problems during their pregnancy, as compared with other chronotypes, in a sample consisting of 1653 pregnant women from the Finnish CHILD-SLEEP Birth Cohort. Chronotype was assessed with a shortened version of the morningness–eveningness questionnaire. Pregnant evening-type women reported more sleep problems, including troubles of falling asleep (OR = 3.4, p < 0.0001), poor sleep quality (OR = 2.9, p < 0.01) and daily tiredness (OR = 3.2, p < 0.0001) than the morning-type women, even after controlling for sleep duration and sleep deprivation. They had higher scores on Epworth Sleepiness Scale ( p < 0.05), Basic Nordic Sleep Questionnaire ( p < 0.0001) and Global Seasonality Score ( p < 0.01) and were also more often smokers, also during pregnancy ( p < 0.001) and reported poorer general health ( p < 0.001) than the morning-type women. They also reported having had more sleep problems during their childhood (OR = 1.5, p < 0.05) and adolescence (OR = 2.0, p < 0.001) than the morning-type women. Our results indicate that eveningness is associated with more sleep problems and unhealthy life habits during pregnancy.